Improving Learning Motivation Through Teams Games Tournament (TGT) Model Integrated with Technology in Biology Learning - Stevany Romaito Lumbantobing; Mursito S. Bialangi; Fetmi Fetmi (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to enhance students’ learning motivation in biology through the implementation of the Teams Games Tournament (TGT) learning model integrated with technology. The research was prompted by the low learning motivation observed among Grade X-7 students at SMA Negeri 7 Palu, most of whom exhibit a kinesthetic learning style that has not been adequately supported by appropriate teaching methods. The study employed a Classroom Action Research approach conducted in two cycles, involving 34 students as participants. The TGT model was applied using educational platforms such as Quizizz, Wordwall, Educaplay, and Kahoot, complemented by reward incentives to boost student engagement. The results revealed a significant increase in students’ learning motivation, as evidenced by both direct observation and motivation questionnaires. In the pre-cycle phase, 3 students were categorized as having low motivation, 23 as moderate, and 8 as high. In Cycle I, 18 students were in the moderate category and 15 in the high category. By Cycle II, 8 students were categorized as moderate, 19 as high, and 7 as very high. The interactive, competitive, and technology-based TGT model proved effective in creating an enjoyable learning atmosphere tailored to students’ characteristics, thereby gradually improving both motivation and learning outcomes. In addition, this study provides a theoretical contribution to the development of collaborative, digital-based learning strategies that align with the demands of 21st-century education. The findings strengthen the theoretical foundation of learning motivation and open up further opportunities for research on the integration of technology into cooperative learning models.